TRANSPARANSI PENGELOLAAN PADA BIAYA PANJAR PERKARA PERDATA DI PENGADILAN NEGERI - Nely, Nely Rahma Wati; Murdiana, Elfa; Ardliansyah, Moelki Fahmi (LPPM STAI DARUSSALAM LAMPUNG, 2024)
Abstract This research is interesting to research because it is directly related to the principles of justice, accountability and community accessibility to justice. Transparency is important to prevent misunderstandings, increase public trust and ensure management complies with regulations. This research aims to analyze the importance of transparency in the legal process at the District Court by examining the mechanism for payment of down payment fees for civil cases, transparency procedures in notification of remaining or shortfall in fees, as well as the follow-up carried out by the District Court upon notification of remaining or shortfall in down payment. This research uses qualitative research methods with a case study that focuses on the Sukadana District Court. This research method was chosen because it allows researchers to explore in depth the transparency of management of down payment fees for civil cases at the District Court. The research results show that there are several policies that have been implemented by the Sukadana District Court to increase transparency in the justice administration process, which includes setting consistent and systematic fee standards for each type of case as well as providing accurate information regarding the amount of the retainer that must be paid. In line with this, notification of the remaining downpayment is conveyed clearly, both through the Case Tracking Information System (SIPP) and directly when the judge's decision is announced. The Sukadana District Court also ensured that the remaining down payment could be easily collected by the litigants, and if it was not collected within 180 days, the money had to be deposited into the state treasury as Non-Tax State Revenue (PNBP). Keywords: Transparency, Case Fees, District Court